Pulsatile lavage systems with high impact pressure and high flow produce cleaner cancellous bone prior to cementation in cemented arthroplasty - Knappe, Kevin; Bitsch, Rudi G.; Schonhoff, Mareike; Walker, Tilman; Renkawitz, Tobias; Jäger, Sebastian (Journal of Clinical Medicine, 2022)
In cemented joint arthroplasty, state-of-the-art cementing techniques include high-pressure pulsatile saline lavage prior to cementation. Even with its outstanding importance in cementation, there are surprisingly few studies regarding the physical parameters that define pulsatile lavage systems. To investigate the parameters of impact pressure, flow rate, frequency and the cleaning effect in cancellous bone, we established a standardized laboratory model. Standardized fat-filled carbon foam specimens representing human cancellous bone were cleaned with three different high-pressure pulsatile lavage systems. Via CT scans before and after cleaning, the cleaning effect was evaluated. All systems showed a cleaning depth of at least 3.0 mm and therefore can be generally recommended to clean cancellous bone in cemented joint arthroplasty. When comparing the three lavage systems, the study showed significant differences regarding cleaning depths and volume, with one system being superior to its peer systems. Regarding the physical parameters, high impact pressure in combination with high flow rate and longer distance to the flushed object seems to be the best combination to improve the cleaning of cancellous bone and therefore increase the chances of a deeper cement penetration that is required in cemented joint arthroplasty. In summary, this study provides the first standardized comparison of different lavage systems and thus gives initial guidance on how to optimally prepare cancellous bone for cemented joint arthroplasty.